Semantic Grid Platform in Support of Engineering Virtual Organisations - Dolenc, M.; Klinc, R.; Turk, Ž.; Katranuschkov, P.; Kurowski, K. (Informatica)
Semantic Grid Platform in Support of Engineering Virtual Organisations